Farmers of the World The Development of Agricultural Extension - Brunner, Edmund Des; Ensminger, Douglas; Sanders, Irwin T. (Columbia University Press, 1945)
Looks at the most effective approach which a government or private agency can use in helping rural people solve their everyday problems, an approach called Extension